The Dynamic Sequential Comprehensive Treatment for Labia Majora Keloids: A Case Report and Literature Review - Kun Yang; Jiayi Fu; Qiang Li (Case Reports in Dermatology)
Introduction: Keloids exhibit persistent growth beyond the original lesion, causing functional and cosmetic impairments. Keloids in the female genital region are especially rare. Case Presentation: This report presents a unique case of bilateral labia majora keloids in a 35-year-old woman, persisting for over 20 years. Given the aesthetic importance of the labia majora, she underwent dynamic sequential comprehensive treatment centered on surgery. The patient was satisfied with the outcome, with no recurrence after 1 year. In addition to reviewing relevant literature, we evaluate the etiology, clinical manifestations, diagnosis, and treatment options for this condition. Conclusion: Dynamic sequential comprehensive treatment centered on surgery is effective in managing labia majora keloids. Emphasizing aesthetic outcomes is crucial. Early diagnosis and proper management are vital for alleviating symptoms and improving quality of life for affected individuals. Further research and increased awareness are essential for better understanding and managing labia majora keloids.